Molecular phylogenetics, systematics and host-plant associations of the Bruchidius albosparsus (Fåhraeus) species group (Coleoptera, Chrysomelidae, Bruchinae) with the description of four new species - Delobel, Alex; Ru, Bruno Le; Genson, Gwenaëlle; Musyoka, Boaz K.; Kergoat, Gael J. (Zootaxa, 2015)
Bruchidius Schilsky is a large paraphyletic genus of seed beetles (Coleoptera: Chrysomelidae: Bruchinae) which consists of multiple lineages that are usually associated with narrow sets of host-plants. In this study we focus on a group that mostly develops on wattle trees (acacias) belonging to the genus Vachellia Wight & Arn. This group originally included nine species and was designated as the Bruchidius centromaculatus (Allard) species group, but recent phylogenetic analyses revealed that these species belong to a much wider group of species with similar morphologies. For reasons of anteriority we call this enlarged group Bruchidius albosparsus (Fåhraeus). Here we review the morphology of species in this group and provide new diagnoses and ecological data for 10 species. The following combinations and synonymies are proposed: Bruchidius tanaensis (Pic, 1921) (= Bruchus tanaensis Pic, 1921) comb. nov. and Bruchidius albosparsus (Fåhraeus, 1839) (= Bruchus spadiceus Fåhraeus, 1839) syn. nov. Four new species are also described: B. eminingensis sp. nov., B. gerrardiicola sp. nov., B. glomeratus sp. nov. and B. haladai sp. nov. Finally we carried out molecular phylogenetic analyses on a multi-marker dataset of 59 specimens and 35 species, including 14 species from the group. The resulting trees allow us to confirm the monophyly of the group of interest and provide a more detailed picture of their evolutionary relationships.